Violence Victimization and Depressive Symptoms Among a Sub-Sample of Sexual and Gender Minority Adults in a Population-Based South African Study - Metheny, Nicholas (Journal of interpersonal violence, 2024)
Sexual and gender minority (SGM) adults in South Africa face high levels of violence and poor mental health outcomes. Interventions to prevent these negative health implications are hampered by a lack of representative data among this population. This study aims to quantify the associations between three forms of violent victimization and depressive symptoms in a sub-sample of SGM drawn from a population-based cross-sectional study in Gauteng, South Africa. Data come from the sixth Quality of Life survey conducted in South Africa’s Gauteng province. Brief screeners assessed childhood sexual abuse (CSA), past-year intimate partner violence (IPV), non-partner violence, and depressive symptoms. Three survey-weighted logistic regression analyses were fit to model associations between elevated depressive symptoms and CSA, past-year IPV, and past-year non-partner violence, controlling for socio-demographics (age, race, sex, area of residence, education, socioeconomic status, and recent employment). N = 1,328 SGM respondents were included. Over 40% (n = 537) reported depressive symptoms, while 17% (n = 222) reported CSA, 5% (n = 67) reported IPV, and 16% (n = 208) reported non-partner violence. CSA and non-partner violence were associated with significantly higher odds of reporting depressive symptoms (aOR: 1.51, 95% CI [1.03, 2.23]; aOR: 1.84, [1.24, 2.73], respectively). IPV was not associated with elevated depressive symptoms (aOR: 1.17, [0.64, 2.16]). In all models, employment in the past 7 days was associated with significantly lower odds of reporting depressive symptoms. Recent and childhood violence is a major burden that is associated with elevated symptoms of depression among SGM in urban South Africa. Community-tailored interventions and policy-related advocacy related to employment and violence prevention may alleviate depressive symptoms in SGM adults in Gauteng.